Towards an Experience-Based Aesthetics of Virtual Reality: A Case Study on Fear (Itinera, 2024)
When developing an aesthetics of VR, it is essential that it remains anchored to concrete objects and actual users’ inclinations and practices. This article provides an example of an “experience-based” aesthetics of VR, presenting the results of a pilot empirical study on fear in VR and discussing it in aesthetic terms. More in particular, the article ventures into two important debates in the field: that around the “paradox of fiction”, and that concerning aesthetic distance. By doing so, the article highlights the fruitfulness of investigating a difficult object like VR, which eludes standard conceptualizations from image and media theory. At the same time, it illustrates how developing a specific aesthetics of VR can contribute in turn to indicate new pathways into long-standing issues in aesthetics as a whole.